PENGARUH KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE), KELELAHAN EMOSIONAL DAN KOMPETENSI TERHADAP KINERJA BIDAN PADA RUMAH SAKIT UMUM DAERAH KABUPATEN MUNA - Dewi Kurniati Aifu; Ansir Ansir; Laode Asfahyadin Aliddin; Sujono Sujono; Zaludin Zaludin (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to examine and explain the effect of Quality of Work Life (Quality of Work Life), Emotional Fatigue and Competence on the Performance of Midwives at the Muna Regency General Hospital. This research approach is a survey with an Explanatory Research design. Data was collected using instruments in the form of data analysis, namely descriptive analysis and inferential statistics, namely Multivariate Regression Analysis. The results of this study state that (1) Quality of Work Life has a positive and significant effect on the performance of midwives, (2) Emotional exhaustion has a positive and insignificant effect on the performance of midwives, (3) Competence has a positive and significant effect on the performance of midwives, (4) Quality of Work Life, Emotional exhaustion and competence simultaneously affect the performance of midwives